Sexual Harassment and Binge Eating Among Chinese Female Undergraduates: A Mediation Model of Self-Objectification and Self-Control - Zheng, Panpan (Journal of interpersonal violence, 2025)
Sexual harassment is a serious health issue prevalent on campuses worldwide, with significant implications for individuals’ well-being. Past research has highlighted the close association between sexual harassment and eating disorders, yet little is known about the mechanisms underlying this relationship. This study aimed to investigate the potential mediating roles of self-objectification and self-control in linking sexual harassment to binge eating, drawing upon objectification theory and self-control resource theory. A sample of 801 Chinese female undergraduates, with a mean age of 19.60 years (SD = 1.42), participated in the study by completing questionnaires on sexual harassment experience, self-objectification, self-control, and binge eating. The results indicated that sexual harassment experience exhibited a significant positive correlation with binge eating and self-objectification, while showing a negative correlation with self-control. And an increased frequency of sexual harassment experiences and self-objectification were associated with lower levels of self-control. Furthermore, mediation analyses utilizing Hayes’ PROCESS macro (2013) for SPSS (Model 6) demonstrated that both self-objectification and self-control independently and sequentially mediated the relationship between sexual harassment and young women’s binge eating. In other words, young women who had experienced sexual harassment were more likely to exhibit increased self-objectification, leading to decreased self-control and ultimately culminating in binge eating behaviors. This study provides valuable insights into how sexual harassment affects young women’s binge eating by elucidating the mediating roles of self-objectification and self-control, thus enhancing our understanding of developing strategies to mitigate the negative consequences of experiencing sexual harassment.